Control of Agricultural Land Function Conversion Toward Food Production Stability With an Interactive Planning Approach in Jombang District - Agustina, Nia Giant Virnanda; Puspaningtyas, Angraeny; Wahyudi, Eddy (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
Agricultural land conversion is one of the problems that affect the vulnerability of food security. This phenomenon, especially on productive agricultural land, continues to occur and has an impact on decreasing food production. This study uses a descriptive research method with a qualitative approach to examine the concept of interactive planning that emphasizes participation and collaboration between stakeholders in managing land conversion that has an impact on the surrounding environment. The purpose of this study is to analyze the application of interactive planning in controlling agricultural land conversion to maintain the stability of food production in Jombang Regency. The results of the study indicate that agricultural land conversion is driven by factors such as population growth and increasing marriage rates, thus increasing the demand for housing and settlement development. Public understanding of the Regional Spatial Plan (RTRW) is still limited, and many development projects are carried out without permits in accordance with statutory provisions. In addition, the Department of Agriculture, which is responsible for managing the agricultural sector, is not involved in the development process related to changes in land use, so that supervision of agricultural land is weak. Steps that can be taken are the implementation of policies in the form of incentives and disincentives for land owners and farmers to minimize agricultural land conversion, especially land designated as Sustainable Food Agricultural Land (LP2B). However, in practice, the enforcement of sanctions is still not optimal because of the sensitivity of land issues in the community. This study recommends stronger enforcement of regulatory policies, including imposing sanctions on parties who carry out development activities that are not in accordance with spatial designations, as well as increasing interactive planning between stakeholders to encourage environmentally friendly sustainable development.